The natural northern European boreal forests: unifying the concepts, terminologies, and their application - Rouvinen, Seppo; Kouki, Jari (Silva Fennica, 2008)
Recent emphasis on conserving the biodiversity has stressed the value of natural ecosystems in saving the species from extinction. In the Fennoscandian region the conifer-dominated boreal forests form the largest single ecosystem. The forests have been under varying intensity of human influence for decades or centuries. Recent attempts have tried to seek the last remaining natural forests to be included in the protection programmes. However, due to long and widespread human influence, finding and defining the natural forests has proven to be extremely difficult, not only because they are so rare but also because the concept of natural forest is vague. These difficulties are partly seen through the diverse terminology used. We first review the varying terminology as seen in recent studies. Secondly, we propose the basis for defining the natural forest and show some intriguing and challenging difficulties are involved in the concept. These difficulties are at least partly related to inherent strong and long-term dynamic component in boreal forest ecosystems that is manifested over several temporal and spatial scales. Finally, we outline a more general terminology with associated indicators and measurements that might be used in the classification and terminology. Conceptual clarification is necessary, for example, to compile ecologically justified and representative global, national and regional forest statistics. Many currently applied definitions of âforestâ and ânaturalâ that are applied in the context of forest statistics overlook ecologically important components of natural forests, and thus provide quite misleading or inadequate data of existing diversity patterns in these ecosystems.